2019
DOI: 10.1016/j.nuclphysa.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Unified framework for heavy flavor and quarkonium production in high multiplicity p+p and p+A collisions at RHIC and LHC

Abstract: We discuss the production of D-mesons and J/ψ in high multiplicity proton-proton and proton-nucleus collisions within the Color-Glass-Condensate (CGC) framework. We demonstrate that the modification of the LHC data on D and J/ψ yields in high multiplicity events relative to minimum bias events arise from a significant enhancement of the gluon saturation scales of the corresponding rare parton configurations in the colliding protons and nuclei. For a given event multiplicity, we predict these relative yields to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…They can nevertheless be modeled by allowing the values of the saturation scales at large x ∼ 0.01 to be larger than those in minimum bias events, and evolving the corresponding distributions to smaller values of x employing the CGC renormalization group framework. In previous studies [3,4], we found that this simple modification of large x initial conditions provides a good description of some features of the data on D-meson and J/ψ production in high multiplicity p + p and p + A collisions at the LHC. In this writeup, we will outline some of the principal results of our work and briefly discuss how the rapidity dependence of the LHC data can further help constrain initial state models of rare events.…”
Section: Introductionmentioning
confidence: 73%
“…They can nevertheless be modeled by allowing the values of the saturation scales at large x ∼ 0.01 to be larger than those in minimum bias events, and evolving the corresponding distributions to smaller values of x employing the CGC renormalization group framework. In previous studies [3,4], we found that this simple modification of large x initial conditions provides a good description of some features of the data on D-meson and J/ψ production in high multiplicity p + p and p + A collisions at the LHC. In this writeup, we will outline some of the principal results of our work and briefly discuss how the rapidity dependence of the LHC data can further help constrain initial state models of rare events.…”
Section: Introductionmentioning
confidence: 73%
“…The factorisation effectively holds for J/ψ in minimum bias pA collisions, but it may break in high-multiplicity events even though the J/ψ is a strongly-bound system. The multiple rescattering effects in the CGC framework can describe high-multiplicity events due to the sizeable semi-hard saturation scale [101,720], although the underlying physics behind such phenomena is still not very clear (Section 2.3.2). In high-multiplicity pA collisions, the nuclear-enhanced-comover-rescattering effect could lead to the modification of J/ψ production rate due to the threshold-sensitive suppression [655].…”
Section: Azimuthal Anisotropies From Initial-state Effectsmentioning
confidence: 99%
“…mesons in the open sector or J/ψ mesons in the hidden sector, and we will generally follow the methods of augmenting CGC calculations with hadronization prescribed in Ref. [55].…”
Section: Hadronization In the Heavy Flavor Sectormentioning
confidence: 99%
“…For the production of heavy quarkonia such as the J/ψ, we will follow the procedure of [55] and employ the Improved Color Evaporation Model (ICEM) [63] to treat the hadronization of a partonic cc pair into a final-state J/ψ. For the hadronization of a single pair, we obtain the hidden heavy flavor analogue of (65):…”
Section: Hadronization In the Heavy Flavor Sectormentioning
confidence: 99%
See 1 more Smart Citation